Cultural Heritage Tourism Development at Goa Gajah, Bedulu Village, Gianyar Regency - Ni Wayan Gita Sadhana Savitri; Made Sera Septiani (Tourism and Hospitality Insights, 2026)
Introduction: Indonesia possesses rich cultural diversity that serves as a key asset in the development of cultural heritage tourism, particularly in Bali Province, where cultural tourism is the core of tourism development. Goa Gajah, located in Bedulu Village, Gianyar Regency, is a cultural heritage site that functions as a living monument as well as a tourist attraction. This study aims to examine the cultural heritage potential of Goa Gajah and analyze its development as a cultural heritage tourism attraction. Methods: This research employed a qualitative approach. Data were collected through direct observation, in-depth interviews, and literature review. Informants were selected using purposive sampling, involving members of the local tourism awareness group (Kelompok Sadar Wisata). Data were analyzed using qualitative data analysis techniques. Results: The findings indicate that Goa Gajah possesses high historical, religious, archaeological, and spiritual values, reflected in the presence of meditation caves, Hindu–Buddhist statues, reliefs, ancient bathing pools, and religious functions that remain active to this day. The development of Goa Gajah tourism is carried out through an integrative approach involving collaboration between the local government, the Cultural Heritage Preservation Authority, and the local community, with a strong emphasis on conservation principles. Conclusion: The development of Goa Gajah as a cultural heritage tourism attraction has significant potential to support sustainable tourism, strengthen local cultural identity, and provide social and economic benefits for the local community while maintaining the preservation of cultural heritage assets.